PENERAPAN MANAJEMEN PENCEGAHAN PENYAKIT DI PETERNAKAN P4S MUPU AMERTA, BANJAR SALE, DESA ABUAN, BANGLI - I K. G., Suyasa; Sarini, N. P.; Lindawati, S. A. (Jurnal Peternakan Tropika, 2016)
This activity aim was to learn aplication of preventive deseases at P4S Mupu Amerta cattle farm, Banjar Sale, Desa Abuan, Bangli as student obligation for apprentice study at Animal Husbandry Faculty, Udayana University. This studi show that Mupu’s farm good preventive deseases  was aplicated, through biosecurity, sanitation, vaccination and others.  Biosecurity measure which is implemented in that farm including permanent stable, apropriate distance to neighberhood, has private equipment and tight selection for visitors. In addition to Biosecurity, Sanitation, was applied not only to make stable clean and tidy but also farm as a hole.  Vaccination, on the other hand, the owner regularly give their catle SE vaccine, vitamin and worm medication. In conclusion, in Mupu’s farm comprehensive preventive deseasses was applied and the student obtain knowledge on deseasses prevention.
Keywords: Management of Preventive Deseases, Biosecurity, Animal Health